Stereotypes and welfare attitudes: a panel survey of how ‘poor Carina’ and ‘lazy Robert’ affected attitudes towards social assistance in Denmark - Troels Fage Hedegaard (Nordic Journal of Social Research)
What is the impact of a predominantly negative debate about social assistance on public and individual support for the social benefit? Over the course of a year the public debate about social assistance flared up twice in Denmark. The debates drew on classic stereotypes of the social assistance recipients lacking both the financial incentives and the will to work. According to theories of the impact of media on welfare attitudes, this had the potential to undermine public support. A two-wave panel survey, however, showed only a small drop in public support for spending on social assistance, in a comparison of attitudes before and after the debates. The small overall impact on public opinion, however, hid a polarization of attitudes on the individual level. This shows that there was not a uniform reaction to welfare debates, but that people tend to seek out a version of reality that is consistent with their values and self-interest. The article thus shows that people when faced with public debates on welfare policies will seek to confirm their personal biases and this limits the possibility for overall changes in public support.